(untitled) (Andamios, Revista de Investigación Social, 2025)
This essay focuses on recognizing the imaginative faculty and the subject’s capacity to symbolically institute their immediate world. The objective is to analyze the social imaginary institutionalization as a significative basis that allows for the plausibility of social saying-doing. Thus, through a theoretical propaedeutic, it shows how social imageries founded in modernity constituted a symbolic structure of adjustment (Baeza, 2015; 2000) that provided stability in the praxis of an era, but now, due to the climate crisis, as an external restriction of the first natural stratum (Castoriadis, 2013), these meanings lack full legitimacy. Therefore, an institutionalizing process is detected that seeks to establish new meanings that fit the current context of the planet.